Association of Positive and Negative Feelings with Anxiety and Depression Symptoms among Computer Science Students during the COVID-19 Pandemic - Soares Passos, Lígia Maria; Murphy, Christian; Chen, Rita Zhen; Santana, Marcos Gonçalves; Passos, Giselle Soares (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2022: Anais do II Simpósio Brasileiro de Educação em Computação, 2022)
The global COVID-19 pandemic has had a significant impact not just on physical health, but also on mental health. Previous studies have demonstrated that Computer Science (CS) students are particularly vulnerable to mental illness. This paper presents a study describing the changes in CS students' positive and negative feelings during the pandemic and social isolation, as well as activities used to cope with this new situation. Our evaluation shows that 81.0% of students reported that their well-being had been negatively affected by the pandemic, with the most reported concerns including social isolation, delay in their academic progress, risk of contamination, and death of loved ones, with discouragement, uncertainty, and stress being the negative feelings that increased the most. Our study also showed that these negative feelings correlated with a higher prevalence of anxiety and depression symptoms, and that the impact was more pronounced in female students than in male students.